Sites of Distant Metastases and Cancer-Specific Survival in Intraductal Papillary Mucinous Neoplasm With Associated Invasive Carcinoma: A Study of 1,178 Patients - Huang, Xiaoyi; You, Siting; Ding, Guiling; Liu, Xingchen; Wang, Jin; Gao, Yisha; Zheng, Jianming (Frontiers in Oncology, 2021)
Background: To explore the impact of distant metastases on cancer-specific survival in patients with intraductal papillary mucinous neoplasm (IPMN) with associated invasive carcinoma and identify the risk factor of distant metastases in IPMN with associated invasive carcinoma. Materials and methods: patients with IPMN with associated invasive carcinoma between 2010 and 2015 were retrospectively selected from the Surveillance, Epidemiology, and End Results (SEER) database. The survival analyses were assessed by Kaplan-Meier analyses and log-rank test. The impact of distant metastases was evaluated by the Cox regression model and the risk factors of distant metastases were identified by logistic regression analyses, respectively. Results: The median cancer-specific survival time of patients with no metastases, isolated liver, isolated lung, and multiple site metastases were 19 months, 4 months, 7 months, and 3 months, respectively. In patients with isolated liver metastases, multivariate analysis after adjustment indicated that chemotherapy (Hazard Ratio [HR]=0.351, 95% confidence interval [CI]=0.256-0.481, P<0.001) was a protective prognostic factor for cancer-specific survival (CSS) in patients with isolated liver metastases. In isolated lung metastases subgroup, old age (HR=1.715, 95% CI=1.037-2.838, P=0.036) and chemotherapy (HR=0.242, 95% CI=0.134-0.435, P<0.001) were related to CSS in multivariable Cox regression analysis(P<0.05). Tumor located in the pancreatic body/tail (HR=2.239, 95% CI=1.140-4.400, P=0.019) and chemotherapy (HR=0.191, 95% CI=0.108-0.340, P<0.001) were independent prognostic factors for CSS in patients with multiple metastases. Finally, a nomogram was constructed for cancer-specific survival and the predicted C-indices was 0.780 (95% CI=0.762-0.798). Conclusion: The liver is the most common site of distant metastases in IPMN with associated invasive carcinoma. Tumor located in the pancreatic body/tail and chemotherapy are independent prognostic factors for CSS in patients with multiple metastases. Further, tumor located in body/tail is identified as a risk factor of distant metastases.